Hypervalent iodine-guided electrophilic substitution: para-selective substitution across aryl iodonium compounds with benzyl groups - Mowdawalla, Cyrus; Ahmed, Faiz; Li, Tian; Pham, Kiet; Dave, Loma; Kim, Grace; Hyatt, I. F. Dempsey (Beilstein Journal of Organic Chemistry, 2018)
The reactivity of benzyl hypervalent iodine intermediates was explored in congruence with the reductive iodonio-Claisen rearrangement (RICR) to show that there may be an underlying mechanism which expands the reasoning behind the previously known C–C bond-forming reaction. By rationalizing the hypervalent iodine’s metal-like properties it was concluded that a transmetallation mechanism could be occurring with metalloid groups such as silicon and boron. Hypervalent iodine reagents such as Zefirov’s reagent, cyclic iodonium reagents, iodosobenzene/BF3, and PhI(OAc)2/BF3 or triflate-based activators were tested. A desirable facet of the reported reaction is that iodine(I) is incorporated into the product thus providing greater atom economy and a valuable functional group handle for further transformations. The altering of the RICR’s ortho-selectivity to form para-selective products with benzyl hypervalent iodine intermediates suggests a mechanism that involves hypervalent iodine-guided electrophilic substitution (HIGES).
Keywords: electrophilic aromatic substitution; hypernucleofugality; hypervalent iodine; iodonio-Claisen; transmetallation

Hypervalent Iodine Chemistry: Preparation, Structure, and Synthetic Applications of Polyvalent Iodine Compounds - Zhdankin, V. V. (John Wiley and Sons, 2013)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Huang, H.; Jia, K.; Chen, Y. (Angew. Chem., Int. Ed., 2015)

(untitled) - Jia, K.; Zhang, F.; Huang, H.; Chen, Y. (J. Am. Chem. Soc., 2016)

(untitled) - Huang, H.; Zhang, G.; Chen, Y. (Angew. Chem., Int. Ed., 2015)

(untitled) - Lee, K.; Kim, D. Y.; Oh, D. Y. (Tetrahedron Lett., 1988)

(untitled) - Ochiai, M.; Fujita, E.; Arimoto, M.; Yamaguchi, H. (Chem. Pharm. Bull., 1985)

(untitled) - Ochiai, M.; Ito, T.; Takaoka, Y.; Masaki, Y. (J. Am. Chem. Soc., 1991)

(untitled) - Khatri, H. R.; Nguyen, H.; Dunaway, J. K.; Zhu, J. (Front. Chem. Sci. Eng., 2015)

(untitled) - Nguyen, H.; Khatri, H. R.; Zhu, J. (Tetrahedron Lett., 2013)

(untitled) - Khatri, H. R.; Zhu, J. (Chem. – Eur. J., 2012)

(untitled) - Shafir, A. (Tetrahedron Lett., 2016)

(untitled) - Izquierdo, S.; Essafi, S.; del Rosal, I.; Vidossich, P.; Pleixats, R.; Vallribera, A.; Ujaque, G.; Lledós, A.; Shafir, A. (J. Am. Chem. Soc., 2016)

(untitled) - Zhao, J.; Li, S. (J. Org. Chem., 2017)

(untitled) - Ochiai, M.; Kida, M.; Okuyama, T. (Tetrahedron Lett., 1998)

(untitled) - Ochiai, M.; Ito, T. (J. Org. Chem., 1996)

(untitled) - Umemoto, T. (Chem. Rev., 1996)

(untitled) - Bachi, M. D.; Bar-Ner, N.; Crittell, C. M.; Stang, P. J.; Williamson, B. L. (J. Org. Chem., 1991)

(untitled) - Stang, P. J. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Stang, P. J.; Surber, B. W.; Chen, Z. C.; Roberts, K. A.; Anderson, A. G. (J. Am. Chem. Soc., 1987)

(untitled) - Zhdankin, V. V.; Scheuller, M. C.; Stang, P. J. (Tetrahedron Lett., 1993)

(untitled) - Zhdankin, V. V.; Crittell, C. M.; Stang, P. J.; Zefirov, N. S. (Tetrahedron Lett., 1990)

(untitled) - Miyata, S.; Hirano, S.; Ohsawa, M.; Kamei, J. (Psychopharmacology (Heidelberg, Ger.), 2011)

(untitled) - Hollister, L. E. (Calif. Med., 1958)

(untitled) - Cavallini, G.; Massarani, E.; Nardi, D.; Mauri, L.; Barzaghi, F.; Mantegazza, P. (J. Am. Chem. Soc., 1959)

(untitled) - Attwood, D. (Adv. Colloid Interface Sci., 1995)